Set distance time trials for predicting maximal aerobic speed in female Australian Rules Footballers. Issue 4 (April 2021) - Lundquist, Mia; Nelson, Maximillian J.; Debenedictis, Thomas; Gollan, Stuart; Fuller, Joel T.; Larwood, Trent; Bellenger, Clint R.
Abstract: Objectives: Maximal aerobic speed (MAS) may be predicted from 2.0 km time trial (TT) running speed in male Australian Rules football (AF) players. Given the between-sex differences in physiological variables precursory to endurance performance, and the impact of this on MAS distance limit, this study determined running speed across various TT distances best approximating MAS in female AF players. Method: 33 female AF players completed assessments of MAS and TT performance separated by at least 48 h. In a randomised order, half of the athletes completed TT distances of 1.2, 1.6 and 2.0 km, and the other half completed distances of 1.4, 1.8 and 2.2 km. Bias, limits of agreement (LOA) and linear mixed modelling determined agreement between TT-derived running speed and MAS. Results: Average speed for all TT distances were different to MAS (bias≥0.59 ± 0.45 km·h −1 ; p ≤ 0.015) with the exception of the 1.4 km TT (bias = −0.12 ± 0.26 km·h −1 ; p = 0.34). LOA was narrowest for the 1.4 km TT (±0.76 km·h −1 ; ±6.1%) compared to other TT distances (±0.82–1.67 km·h −1 ; ±6.7–12.9%). A significant linear association between bias and TT distance (r = −0.73; p < 0.001) indicated TT speed would be equal to MAS when a 1.4–1.5 km TT was completed, and that MAS may be predicted from any distance between 1.2 and 2.2 km. Conclusions: MAS was best approximated by a 1.4–1.5 km TT in female AF players, but may be predicted from TT speed for any distance between 1.2 and 2.2 km. TT-derived MAS provides a time and resource efficient method for the quantification of aerobic fitness and prescription of future training intensities.